2018
DOI: 10.1002/pbc.27288
|View full text |Cite
|
Sign up to set email alerts
|

Unfavorable presentation but comparable outcome: Presentation and outcome of children with nodular lymphocyte predominant Hodgkin lymphoma from India

Abstract: NLPHL in India has an excellent outcome, despite a higher incidence of unfavorable presentations such as advanced stage disease, B symptoms, and bulky disease. Variant histology is an adverse prognostic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
2
1
1
Order By: Relevance
“…Types A, C, and E of Fan's classification were the most prevalent types, respectively. The rate of typical morphology varies in different studies ranging between 47 and 78% [7,8,10,23]. Some studies have reported a higher rate of typical morphology than the current results [8,23].…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Types A, C, and E of Fan's classification were the most prevalent types, respectively. The rate of typical morphology varies in different studies ranging between 47 and 78% [7,8,10,23]. Some studies have reported a higher rate of typical morphology than the current results [8,23].…”
Section: Discussioncontrasting
confidence: 59%
“…The rate of typical morphology varies in different studies ranging between 47 and 78% [7,8,10,23]. Some studies have reported a higher rate of typical morphology than the current results [8,23]. Hartmann et al studied 423 NLPHL cases and reported that 72% of their patients showed a typical morphological pattern [7].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…В части работ, выполненных преимущественно во взрослой популяции, показано, что у пациентов с атипичными паттернами чаще отмечаются неблагоприятное клиническое течение, инициально продвинутая стадия, плохой ответ на проводимую терапию, частое развитие рецидивов по сравнению с пациентами с типичными паттернами [35][36][37][38]. В детской популяции данные работы единичны [39][40][41].…”
unclassified